SOCIAL ENTREPRENEURSHIP AS ONE OF THE BUSINESS DEVELOPMENT ACTIVITIES IN RURAL AREAS OF LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Since 1 of April 2018, it is possible to register social entrepreneurship in Latvia as one of the type of business and to take advantage that is only suitable for this type of business. The study analyses how coud social entrepreneurship become one of the opportunities to address social problems, directly in rural areas, where today in Latvia is concentrated the largest population of a socially unprotected groups. This means that, while developing social enterprises and solving social problems in the regions of Latvia, at the same time, also address other issues that are actual today – lack of labour force. For entrepreneurs in rural areas, the lack of labour is the most significant, and there is no problem in Latvian regions with finding a place of residence. The development of social entrepreneurship would also be a contributory factor in the fact that the new generation would not leave the countryside, but try to build up their business using existing infrastructure, including a rural school, kindergarten – it helps to them continue to work as well. In the Latvian countryside most are farmers and crafts companies, whose business is most often expressed seasonality. At the rural areas farmers can support with works during sowing and harvesting, and some works during growing period on organic farms. There is also a growing lack of labour force in the sales companies who support farmers with new technologies, especially in aftersales – service departments. Social entrepreneurship could be one of the solutions, especially since it is very seasonal for repairs, so that it is possible to focus the work on the season by successfully management with the contingent in the countryside. There is a great opportunities to make cooperation with local authorities on this issue, the role of the social business in the development and social Affairs of the rural environment should be clarified. As a result of successful cooperation, social enterprises can become an important contribution to local authorities in addressing the societal challenges of the municipality. The study analyses how important to develop this model of cooperation, as it needs to convince local leaders before work on regional reform begins.